AN EXPERİMENTAL RESEARCH ON INTERGENERATİONAL DETERMİNATİON OF COMPULSİVE PURCHASİNG BEHAVİOR LEVELS AND FORMS (Third Sector Social Economic Review, 2020)
Compulsive buying behavior is a common behavior disorder in late modernist societies. The remarkable aspect of this behavior is that it involuntarily reveals the intolerable and impulsive desire of consumers to buy. Individuals who exhibit compulsive buying behavior see this as a way to reduce their shopping-related stress. People who can be evaluated in this group often experience a decrease in stress levels after shopping, whereas this feeling of saturation after a certain period of time is replaced by guilt, irritability, unhappiness or feeling before buying behavior. This inner cycle continues until we make a new shopping.This study was applied to 401 subjects from X and Y generations selected by easy sampling method in Istanbul metropolis. As a result of the factor analysis applied to the research scale, the rate of explaining the compulsive buying behavior patterns and levels of the five different dimensions was calculated as 59.85%. According to the analysis to determine the differences between the generations, it was found that the dimensions of compulsive buying behavior did not show significant difference between the post-shopping guilt and pleasure and entertainment-oriented spending. In addition, compulsive purchasing dimensions showed a significant difference in terms of ""Spending Tendency"", ""Non-Functional Expenditures"" and ""Expenditure Obligation"".
Keywords: Compulsive Buying; Uncontrolled Shopping; Difference Between Generations; Consumer Behaviour